Peran PAI dalam Menanamkan Nilai Tanggung Jawab dan Disiplin melalui Pembiasaan Ibadah - rusdiahroitonanasution rusdiah; Siti Saroh Hasibuan (GHIROH, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) in instilling values of responsibility and discipline through habitual worship in the school environment. The main issue examined is the extent to which routine worship activities such as congregational prayer, recitation of the Qur'an, and communal prayer can shape students' character in terms of discipline and responsibility. This study uses the library research method by analyzing literature in the form of journals, books, and scientific articles from 2018 to 2025. The results of the study show that structured and consistent worship habits contribute significantly to improving students' discipline, time awareness, and sense of responsibility. In addition, the role of PAI teachers as role models and facilitators is a determining factor in the successful internalization of religious character values in schools.